2006
DOI: 10.4049/jimmunol.177.7.4679
|View full text |Cite
|
Sign up to set email alerts
|

Specific Recognition of Candida albicans by Macrophages Requires Galectin-3 to Discriminate Saccharomyces cerevisiae and Needs Association with TLR2 for Signaling

Abstract: Stimulation of cells of the macrophage lineage is a crucial step in the sensing of yeasts by the immune system. Glycans present in both Candida albicans and Saccharomyces cerevisiae cell walls have been shown to act as ligands for different receptors leading to different stimulating pathways, some of which need receptor co-involvement. However, among these ligand-receptor couples, none has been shown to discriminate the pathogenic yeast C. albicans. We explored the role of galectin-3, which binds C. albicans β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
179
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(187 citation statements)
references
References 58 publications
(53 reference statements)
3
179
0
5
Order By: Relevance
“…Indeed other lectins have been shown to cooperate with TLR-driven pathways, culminating in enhanced cytokine production [39,40]. Recently, galectin-3 was found to be coprecipitated with TLR2 in THP-1 cells after incubation with C. albicans blastoconidia, suggesting that galectin-3 may be associated with TLR2 at the membrane and following interaction with the yeast [21]. However, it was also shown that gal3 À/À macrophages produced lower amounts of TNF-a after incubation with C. albicans, compared with gal3 1/1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed other lectins have been shown to cooperate with TLR-driven pathways, culminating in enhanced cytokine production [39,40]. Recently, galectin-3 was found to be coprecipitated with TLR2 in THP-1 cells after incubation with C. albicans blastoconidia, suggesting that galectin-3 may be associated with TLR2 at the membrane and following interaction with the yeast [21]. However, it was also shown that gal3 À/À macrophages produced lower amounts of TNF-a after incubation with C. albicans, compared with gal3 1/1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, galectin-3 and TLR2 have been found to be associated in C. albicans-infected differentiated macrophages, an association that has been considered essential for TLR2-dependent cytokine production in response to the fungal infection [21]. Therefore, galectin-3 has been considered as a novel pattern recognition receptor, acting either alone or in concert with Toll-like receptors (TLR).…”
Section: Introductionmentioning
confidence: 99%
“…134 Galectin-3 on the surface of murine macrophages specifically recognizes C. albicans, which needs the association of TLR2 for signaling. 108 Interestingly, Galectin-3 also works in association with Dectin-1 on macrophages. 135 When macrophages expressing Dectin-1 are exposed to C. albicans mutants with increased exposure of b-glucan, the loss of Galectin-3 dramatically accentuates the failure to trigger an appropriate TNF-a response.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…23 Galectin-3 on the surface of murine macrophages can bind to the b-1,2 mannosides of C. albicans. 107,108 In human neutrophil, Galectin-3 plays an important role in phagocytosing C. albicans hyphae, but not C. albicans yeasts. 109 Dectin-2 is another PRR for phagocytic cells to recognize C. albicans mannans.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…Gal-3 has been shown to interact with dectin-1 and TLR-2. 77,78 Previous studies using knockout mice have demonstrated that TGF-b1 and IL-6 fuel Th17 differentiation, while IL-23 facilitates the differentiation and sustains the Th17 cells. [79][80][81] IL-17A acts on a variety of cell types to promote inflammation 82 and helps eradicate extracellular pathogens.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%